Avaliação da resistência de união de sistemas adesivos universais à dentina humana, utilizando diferentes estratégias de adesão - Daniel Jose Braga Dutra (2018)
Evaluation of resistance of union of universal adhesive systems to human dentine, using different adhesion strategies In dentistry, innovations in the field of adhesion are observed. Universal multi-mode adhesive systems have been designed under the all-in-one concept of an existing onestep self-etching adhesive system, but incorporating versatility in how it is applied and interacted with the dentin substrate. The universal adhesive allows the dentist to make an adhesive strategy decision: conventional preconditioning method, self-etching technique (without prior acid conditioning) or selective acidification in enamel. This new system, despite representing an interesting innovation in the field of adhesion, still raises questions about its clinical and laboratory performance, mainly due to the different possibilities of protocol presented by the manufacturers. The objective of the present work was to evaluate, through the microtensile test, a bond strength to the human dentin of two universal adhesive systems: Single Bond Universal (3M ESPE) (SBU) and Ambar Universal (FGM) in different therapeutic steps (preconditioning the dentin and maintenance of dry dentin, preconditioning the dentin and maintenance of wet dentin and self-etching mode). In this in vitro laboratory quantitative study, 36 teeth were prepared in the most diverse adhesive strategies and with the use of two commercial brands. They were randomly divided into 6 groups (n = 6), obtaining at least 7 sticks per tooth. Data were considered by the ANOVA test (p <0.05). The individual comparisons were performed with the Tukey's Difference Test (HSD) (p <0.05). The results revealed the difference between groups 1 and 2 (SBU in wet dentin) and also between groups 1 and 3 (SBU in self-etching mode) in relation to the values of microtraction. The adhesive AU did not demonstrate good performance when used in self-etching strategies and with prior acid etching of the dentin and maintenance of the dry dentin. The AU adhesive did not demonstrate good performance when used in the self-etching strategies and with preconditioning the dentin and maintenance of dry dentin. Microscopic analysis revealed that the cohesive and mixed faults predominated in the groups with the acidic conditioning groups of the SBU. In contrast, the selfetching group showed a predominance of adhesive failures. The conventional strategy adhesive in wet dentin demonstrated better performance in the tensile test in both adhesives, the use of the self-etching strategy with the SBU demonstrated promising results, making future analysis necessary.